The Role of Middle Class in Economic Development: What Do Cross-Country Data Show? - Chun, Natalie; Hasan, Rana; Rahman, Muhammad Habibur; Ulubaşoğlu, Mehmet Ali (WILEY, 2017)
This paper investigates the channels through which the middle class may matter for consumption growth. Using several different middle-class measures and a panel of 105 developing countries spanning the period 1985–2013, we find that a larger middle class influences consumption growth primarily through higher levels of human capital accumulation. There is also a significant direct effect of middle-class size on consumption growth, which is more pronounced in the latter half of the sample, the 2000–2013 period.